China's changing economy: implications for its carbon dioxide emissions. (19th May 2017) - Green, Fergus; Stern, Nicholas
Abstract : As China's government unveils the country's 13th Five Year Plan for economic development (2016–2020), this article takes stock of recent changes in China's economy and energy system since the turn of the century, and looks ahead to the likely trajectory of China's emissions over the next decade. It is now clear that the period 2000–2013 was a distinct and exceptional phase in China's developmental history, during which the very high levels of GHGs emitted were linked closely with the energy-intensive, heavy industry-based growth model pursued at that time. China is currently undergoing another major structural transformation – towards a new development model focused on achieving better-quality growth that is more sustainable and inclusive – and it is also grappling with the economic challenges associated with this transition. Data from 2014 and the first three quarters of 2015 illustrate the extent of these changes. Based on analysis of this data in light of the underlying changes occurring in China's economy and policy, this article provides an updated forecast of the Kaya components of energy CO2 emissions (GDP, energy/GDP and CO2 /energy) over the next decade to 2025. It concludes that China's CO2 emissions from energy, if they grow at all, are likely to grow at a much slower rate than under the old economic model and are likely to peak at some point in the decade before 2025. Policy relevance The article suggests a number of important areas of Chinese policy that should be focused on to mitigate the risks and challenges that might otherwise delay the date for peak CO2 emissions. Our analysis and conclusions also have more general implications for Chinese and international climate policy. They suggest that China's international commitment to peak emissions 'around 2030' should be seen as a highly conservative upper limit from a government that prefers to under-promise and over-deliver. They also reinforce the virtue of a 'dynamic' approach to international climate cooperation, as envisaged under the Paris Agreement, whereby countries' targets and policies are regularly updated in light of new information. The importance of macroeconomic analysis for emissions projections and climate policy development is also highlighted.